2013
DOI: 10.1002/jbm.a.34953
|View full text |Cite
|
Sign up to set email alerts
|

Biological behavior of neurally differentiated periodontal ligament stem cells on different titanium implant surfaces

Abstract: We investigated the biological behavior of periodontal ligament stem cells (PDLSCs) induced to differentiate into Schwann cells (SCs) on the surfaces of titanium discs. Two types of titanium surfaces, sand blasted and acid etched (SA) and smooth polished, were prepared on titanium discs, and the behavior of SC-like cells on these discs was investigated. Cell morphology was examined by scanning electron microscopy, and cell proliferation was assessed using assays for methylthiazol tetrazolium metabolism and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition, Adrb2 expression was further confirmed in isolated and expanded PDLCs derived from the neural crest where the SNS originated. PDL-derived stem cells express neural crest cell–specific markers and can be induced to form neural crest-like cells (Coura et al , 2008; Dupin and Coelho-Aguiar, 2013; Fortino et al , 2014; Xiaojie et al , 2014), which implies a close connection between PDLCs and SNS in Adrb2 expression. Static compressive force in vitro upregulated the expression of Adrb2 in PDLCs as force was increased and force-treated time was prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Adrb2 expression was further confirmed in isolated and expanded PDLCs derived from the neural crest where the SNS originated. PDL-derived stem cells express neural crest cell–specific markers and can be induced to form neural crest-like cells (Coura et al , 2008; Dupin and Coelho-Aguiar, 2013; Fortino et al , 2014; Xiaojie et al , 2014), which implies a close connection between PDLCs and SNS in Adrb2 expression. Static compressive force in vitro upregulated the expression of Adrb2 in PDLCs as force was increased and force-treated time was prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…They used PDLSCs instead of SCs due to difficulties obtaining pure and ample sources of SCs. The study showed that the differentiated PDLSCs had the highest expression of SC markers and proteins on the SA titanium surface [ 79 ].…”
Section: Peripheral Nerve System Treatmentmentioning
confidence: 99%
“…[3][4][5] In our previous study, we found that periodontal ligament stem cells (PDLSCs) isolated from beagle dogs effectively differentiated into SCs with exposure to a combination of dimethyl sulfoxide (DMSO), basic fibroblast growth factor (bFGF), brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF) and forskolin. 6,7 Multiple signaling pathways, transcription factors, and neurotrophic factors had been implicated in their differentiation. 3,8 However, the mechanisms underlying the process of PDLSC differentiation to SCs are poorly characterized.…”
Section: Introductionmentioning
confidence: 99%